2020
DOI: 10.1021/acsami.0c08480
|View full text |Cite
|
Sign up to set email alerts
|

Preserving High-Efficiency Luminescence Characteristics of an Aggregation-Induced Emission-Active Fluorophore in Thermostable Amorphous Polymers

Abstract: Luminophores usually suffer from luminescent quenching when introduced into a polymer backbone or side chain, which leads to the inefficient luminescence or even no luminescence of the polymer. In this work, alicyclic imide rings were found to be capable of balancing the donor–acceptor properties between the rigid spacer and the aggregation-induced emission-active fluorophore in light-emitting polymers. Along with the nonplanar and rigid emitter, the suppressed intramolecular charge-transfer effect and interch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…To suppress the CT and LE(n−π*) transitions and enhance the LE(π−π*) transitions between the S 0 and S 1 states, we have developed a series of highly fluorescent PIs with high Φ values by combining dianhydrides with high electron-accepting ability, whose HOMO-LUMO transitions are LE(π−π*), and alicyclic diamines with low electrondonating ability [15,[20][21][22][23][24][25][26][27][28][29]. With other methods, highly fluorescent fully aromatic PIs have been developed by introducing aggregation-induced emission (AIE)-active bulky moieties, such as modified triarylamine [30,31] or tetraphenylethylene structures [32], in their main or side chains.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress the CT and LE(n−π*) transitions and enhance the LE(π−π*) transitions between the S 0 and S 1 states, we have developed a series of highly fluorescent PIs with high Φ values by combining dianhydrides with high electron-accepting ability, whose HOMO-LUMO transitions are LE(π−π*), and alicyclic diamines with low electrondonating ability [15,[20][21][22][23][24][25][26][27][28][29]. With other methods, highly fluorescent fully aromatic PIs have been developed by introducing aggregation-induced emission (AIE)-active bulky moieties, such as modified triarylamine [30,31] or tetraphenylethylene structures [32], in their main or side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Yu-Jen Shao and Guey-Sheng Liou* DOI: 10.1002/adom.202101949 luminogen, 4-cyanotriphenylaminebased diamine (CN-TPA). [6] Zhang et al reported that Al-PI derived from AIEactive 5′-(1,2,2-triphenylvinyl)-[1,1′:3′,1′′terphenyl]-3,3′′-diamine (PhTPEmDA) exhibits high Φ PL up to 89%, [7] whereas the Φ PL of the corresponding Ar-PIs obtained from the same diamine of PhTPEmDA and aromatic dianhydrides was drastically suppressed to lower than 5% or was even non-emissive.…”
Section: Triarylamine-based Wholly Aromatic Polyimide With Simultaneously Unprecedented Photoluminescence Efficiency and High Glass-transmentioning
confidence: 99%
“…Although several approaches have been employed to promote the Φ PL of Ar-PIs, the Φ PL remains weak, and the thermal properties of Ar-PIs are typically poor. Therefore, some researchers have explored incorporating bulky or twisted groups into the side or main chain (e.g., naphthalene, anthracene, pyrene, fluorene, and tetraphenylethylene) [7,8] or designed a donor-acceptor (D-A) structure within diamine or dianhydride moieties to suppress the intermolecular and intramolecular CT effects. [9] By merging these two crucial strategies, we prepared a series of Ar-PIs with high Φ PL derived from electron-donating triarylaminebased dianhydrides with bulky pendant groups (naphthalene and pyrene), and the resulting Ar-PI with naphthalene unit exhibited a Φ PL of 22%.…”
Section: Triarylamine-based Wholly Aromatic Polyimide With Simultaneously Unprecedented Photoluminescence Efficiency and High Glass-transmentioning
confidence: 99%
“…Recently,our group proposed asimple strategy for achieving highly fluorescent PI materials by appropriate control of intramolecular charge transfer effects between diamine and dianhydride moieties, [11] as well as precise controlling of optical properties of fluorescent PI materials through appropriate monomer design. [12] In this work, we report aseries of nonconjugated PI-based fluorescent polymers with TADF property,w hich afford solution-processed PLEDs with very high device efficiencies (EQE up to 21 %) comparable to that of small-molecule counterparts.T othe best of our knowledge, this is the first work presenting TADF-featured PI-based fluorescent polymers and the highest device efficiencies among nonconjugated TADF-based PLEDs.…”
Section: Introductionmentioning
confidence: 98%
“…With regard to PLED applications, a challenging area in the field of PIs is the development of high‐efficiency PI‐based fluorescent polymers to construct high‐performance PLEDs. Recently, our group proposed a simple strategy for achieving highly fluorescent PI materials by appropriate control of intramolecular charge transfer effects between diamine and dianhydride moieties, [11] as well as precise controlling of optical properties of fluorescent PI materials through appropriate monomer design [12] . In this work, we report a series of nonconjugated PI‐based fluorescent polymers with TADF property, which afford solution‐processed PLEDs with very high device efficiencies (EQE up to 21 %) comparable to that of small‐molecule counterparts.…”
Section: Introductionmentioning
confidence: 99%